The Transformation of Teenagers Attitudes Toward Sexual Harassment Through Psychoeducational Video Interventions - Prayoga, Albin; Normaliza Putri, Anggi; Attariq Fadjri, Khalieva; Thanti Syahwani, Marisa; Zahra Aulia Hakim, Nayla; Muthi Annisa, Nida; Eka Aulianti, Jihan (Communication in Research and Publications (CRP), 2025)
Sexual harassment among adolescents is a growing concern, particularly within school environments. Bandung has been identified as one of the regions with the highest rates of sexual violence in West Java, indicating a critical need for effective educational interventions. One promising method is psychoeducational video, which has the potential to engage students emotionally, capture their attention, and enhance memory retention. This study employed a quasi-experimental one-group pretest-posttest design involving 21 eighth-grade students from a public junior high school in Bandung, selected using purposive sampling. The instrument used was the Sexual Harassment Attitude Scale (SHAS), with a reliability coefficient of α 0.871. The results of the analysis show that psychoeducation in the form of videos has a significant influence on changes in students' attitudes regarding sexual harassment with a significance value (p = 0,031). That is, the results show that after watching the psychoeducational video, there is a real change in attitude in students in the form of a more conscious, critical, and non-permissive attitude towards sexual harassment.